Dispute resolution outside of courts: Procedural justice and decision acceptance among users of ombuds services in the UK - Creutzfeldt, N; Bradford, B (Wiley, 2016)
Attitudes towards legal authorities based on theories of procedural justice have been explored extensively in the criminal and civil justice systems. This has provided considerable empirical evidence concerning the importance of trust and legitimacy in generating cooperation, compliance and decision acceptance. However, not enough attention has been paid to attitudes towards institutions of informal dispute resolution. This paper asks whether the theory of procedural justice applies to the alternative dispute resolution (ADR) context, focusing on ombuds services. What are the predictors of perceptions of procedural justice during the process of dealing with an ombuds, and what factors shape outcome acceptance? These questions are analyzed using a sample of recent ombuds users. The results indicate that outcome favorability is highly correlated with perceived procedural justice, and both predict decision acceptance.